Genetic variability and heritability of yield and related characters in yard-long bean - Vidya, C.; Oommen, Sunny K.; Kumar, Vijayaraghava (Journal of Tropical Agriculture, 2006)
Fifty varieties of yard-long bean were evaluated for yield and a few related characters in a field experiment in randomized block design with three replications during rabi season, 1999. Analysis of variance revealed significant differences among varieties for all the characters studied. High genotypic coefficient of variation, heritability in broad sense and genetic advance estimated for the characters viz., yield of vegetable pods per plant, number of pods per plant and pod weight indicated the scope for improvement of these characters through selection.